Coronary artery disease secondary to familial hypercholesterolaemia: An infrequent cause of increasingly common pregnancy co-morbidity. (September 2015) - Varnier, Nicla A; Pettit, Franzisca; Rees, David; Thou, Steven; Brown, Mark; Henry, Amanda
Background: Cardiovascular disease affects 0.2–4% of pregnancies. Coupled with the physiological stress of pregnancy, cardiovascular disease may present significant management challenges including appropriate risk:benefit analysis of medical and surgical management options. Case: A 33-year-old gravida 4 para 1 miscarriage 2 presented at 18 weeks' gestation to the high-risk pregnancy service with a history of coronary artery disease and homozygous familial hypercholesterolaemia. Pre-pregnancy echocardiogram showed probable aortic xanthoma and preserved cardiac function. Prior to planned interventional cardiology assessment for her coronary artery disease she became pregnant, taking aspirin and multivitamins only. She had exertional angina responsive to metoprolol, agreed to recommencing statin therapy when serum cholesterol worsened, but declined angiography during pregnancy. At 36 weeks' gestation, she had further angina symptoms but no acute coronary syndrome. Induction in the High Dependency Unit with elective assisted vaginal delivery of a healthy female infant (birthweight 2460 g) occurred at 37 weeks. She underwent triple-vessel coronary artery bypass postpartum, recovering well. Conclusion: Whilst this specific condition is rare, the increase in cardiovascular disease and cardiovascular risks in the obstetric population emphasises the need for clear, multidisciplinary management from the outset of pregnancy for these women.